ANALISIS MODEL AISDALSLove : HIERARKI EFEK RESPONS KONSUMEN TERHADAP LOGO HALAL BARU INDONESIA - Hijrah Wahyudi; Mardiyati Mardiyati (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2023)
This study aims to analyze the hierarchical effect of consumer responses to Indonesia's new halal logo using the AISDALSLove model. The data analysis technique used was the Total Category Rating (TCR) with a total of 200 respondents who were taken using a purposive sampling technique. The results showed that the variable awareness has the highest rating rate of 84.30%, while the variable desire and like has the lowest rating rate of 80.10%. This shows that consumers have high awareness of Indonesia's new halal logo and the importance of halal certification in food and beverage products. However, the level of consumer desire and preference in buying products containing the new Indonesian halal logo still needs to be improved. Thus, food and beverage companies need to continue to improve the quality of their halal products and strengthen marketing and education campaigns regarding the new Indonesian halal logo to increase the level of consumer desire and preference in buying halal products. This research is expected to contribute to the food and beverage industry in increasing consumer confidence in local halal products.